Good Agricultural Practices (GAP)모델 개발을 위한 부추 및 생산환경에서의 위해요소 조사 - 박상곤; 최영동; 이채원; 정명진; 김정숙; 정덕화; 심원보; Park, Sang-Gon; Choi, Young-Dong; Lee, Chae-Won; Jeong, Myeong-Jin; Kim, Jeong-Sook; et al. (Han'gug sigpum wi'saeng anjeonseong haghoeji, 2015)
This study is to investigate microbiological hazards which can be used as fundamental data to adequately control leeks hazards and develop leeks GAP model for those who want to get GAP system. The microbiological investigations on cultivation environments (soil and water), crops (leeks), personal hygiene (workers' hands, clothes and gloves) and working tools (boxes) have been conducted for one year, so the period was classified under non-cultivation, cultivation, and post harvest. Total bacteria was detected from soil (4.0~6.7 log CFU/g), leeks (4.6~5.1 log CFU/g), hands (ND~3.3 log CFU/hand) and gloves ($ND{\sim}5.4\;log\;CFU/cm^2$) while nothing was detected from the other samples. The coliform contamination of leeks (4.8~5.0 log CFU/g) was more high than that of soil (3.9~4.2 log CFU/g). In case of foodborne pathogens, only B. cereus was detected at the level of 0.5~4.6 log CFU/g (or hand, $100cm^2$). Fungi was observed at the level of 2.1~3.8 log CFU/g (or hand, $100cm^2$) excepting water and some working tools. These results demonstrate that the contamination of leeks is comparatively higher than that of soil sample. The reason may be the cross-contamination by biological hazards presenting on soil. Therefore, it is necessary to properly control soil and fertilizer for safety against biological hazards. 부추의 위해요소관리를 위한 GAP 모델 개발에 필요한 기초 자료로 활용하기 위해 부추 생산과정을 재배전 단계, 재배단계 및 수확 포장단계로 나누어 재배환경 (토양, 용수), 부추, 개인위생 시료에 대해 위생지표세균, 병원성 미생물, 곰팡이의 오염도를 조사하였다. 위생지표 세균 중 일반세균은 토양 6.4~6.7 log CFU/g, 부추 4.6~5.1 log CFU/g, 개인위생 중 손과 장갑에서 각각 최대 3.3 및 5.4 log CFU/hand or $cm^2$으로 검출되었고, 그 외의 시료에서는 2.7 log CFU/g (or mL, hand, $100cm^2$) 이하로 검출되었다. 대장균군은 토양 3.9~4.2 log CFU/g, 부추 4.8~5.0 log CFU/g으로 부추에서 더 높은 수준으로 검출되었고, 대장균은 모든 시료에서 불검출 되었다. 병원성 미생물의 경우 B. cereus만 용수를 제외한 시료에서 0.5~4.6 log CFU/g (or hand, $100cm^2$) 수준으로 검출되었다. 곰팡이의 경우도 용수와 일부 작업도구를 제외한 시료에서 2.1~3.8 log CFU/g (or hand, $100cm^2$) 수준으로 검출되었다. 전반적으로 토양과 닿아 있는 부추에서의 미생물 오염도가 높게 확인되었으며, 이는 비교적 미생물의 오염도가 높은 토양으로부터 교차오염이 발생하였기 때문인 것으로 판단된다. 따라서 부추의 생물학적 위해요소에 대한 안전성 확보를 위해서는 토양 관리가 중요할 것으로 생각 된다.